2019
DOI: 10.15640/jsbed.v7n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Women Entrepreneurs and the Influence of Social Networks on Small Business Outcomes

Abstract: Nascent entrepreneurs must leverage valuable resources, including human, financial, intellectual, and social capital in order to increase the likelihood of success. With the rise of networking technologies such as LinkedIn, Biznik, Cofoundr, and Facebook, social network analysis, long utilized as a method for organizational analysis, has taken center stage in popular understanding of entrepreneurial success. The composition and quality of social networks, however, varies among male and female entrepreneurs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Efficient social networking is key to entrepreneurial success (Taormina & Lao, 2007). Upton and Broming (2019) indicated that social networking assists entrepreneurs in achieving their economic activities and growing their business opportunities. Building strong social networks among entrepreneurs is essential because it helps them expand their knowledge, meet partners to start businesses, and find new resources (Higgins & Pinelli, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Efficient social networking is key to entrepreneurial success (Taormina & Lao, 2007). Upton and Broming (2019) indicated that social networking assists entrepreneurs in achieving their economic activities and growing their business opportunities. Building strong social networks among entrepreneurs is essential because it helps them expand their knowledge, meet partners to start businesses, and find new resources (Higgins & Pinelli, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In the planning stage, entrepreneurs seek to access human and financial capital by accessing their largest social networks. In the establishment phase, entrepreneurs concentrate primarily on their business activities and do not rely on their networks (Upton III et al, 2014). Some individuals avoid constraints in their businesses by using informal relations at the beginning of their business.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the direct conversion of ethanol into ethylene is not likely to be an economically interesting process by itself, but it may play an intermediate role in the synthesis of several of the more economically promising products (Figure ) discussed in the following sections. However, we note that Axen’s Atol process targets ethylene (in combination with their Futurol technology for cellulosic ethanol production). , …”
Section: Chemical Derivatives From Ethanolmentioning
confidence: 99%